2019
DOI: 10.3390/ijms20122897
|View full text |Cite
|
Sign up to set email alerts
|

Role of Leukotriene B4 Receptor-2 in Mast Cells in Allergic Airway Inflammation

Abstract: Mast cells are effector cells in the immune system that play an important role in the allergic airway inflammation. Recently, it was reported that BLT2, a low-affinity leukotriene (LT) B4 receptor, plays a pivotal role in the pathogenesis of allergic airway inflammation through its action in mast cells. We observed that highly elevated expression levels of BLT2 are critical for the pathogenesis leading to allergic airway inflammation, and that if BLT2 expression is downregulated by siBLT2-mediated knockdown, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 59 publications
0
8
0
1
Order By: Relevance
“…Furthermore, several modulated chemokines are associated with pulmonary inflammatory processes. In LPS-stimulated CD8 + T cells, Tα1 downregulated LTB4R2 and CCL2 , which play a pivotal role in the pathogenesis of airway inflammation [ 41 ] and ARDS [ 42 ]. In COVID-19 blood cells, Tα1 downmodulated the transcriptional expression of CCL2 and slightly downmodulated CXCL6 , chemokines involved in fibrosis and leucocytes recruitment [ 41–43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, several modulated chemokines are associated with pulmonary inflammatory processes. In LPS-stimulated CD8 + T cells, Tα1 downregulated LTB4R2 and CCL2 , which play a pivotal role in the pathogenesis of airway inflammation [ 41 ] and ARDS [ 42 ]. In COVID-19 blood cells, Tα1 downmodulated the transcriptional expression of CCL2 and slightly downmodulated CXCL6 , chemokines involved in fibrosis and leucocytes recruitment [ 41–43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Engagement of BLT 2 mediates the synthesis of the most potent proangiogenic molecule, vascular endothelial growth factor (VEGF-A), and IL-13 from mast cells. The authors speculate that novel strategies aimed to block BTL 2 could contribute to the treatment of allergic disorders [50].…”
Section: Prefacementioning
confidence: 99%
“…Engagement of BLT 2 mediates the synthesis of the most potent proangiogenic molecule, vascular endothelial growth factor (VEGF-A), and IL-13 from mast cells. The authors speculate that novel strategies aimed to block BTL 2 could contribute to the treatment of allergic disorders [50].It is well established that mast cells are strategically localized in different sections of the human heart, such as the myocardium [51,52], the atherosclerotic plaque [33], and the aortic valve [53]. Kovanen comprehensively reviews the complex role of mast cells throughout the progression of early to late lesions of human atherosclerosis [32].…”
mentioning
confidence: 99%
“…Moreover, recent reports have indicated that the BLT2 signaling cascade is associated with lung inflammatory diseases such as asthma 17 , 18 . Additionally, BLT2 and its ligand-producing enzymes 5-lipoxygenase (5-LOX) and 12-lipoxygenase (12-LOX), which convert arachidonic acid into the BLT2 ligands LTB 4 and 12( S )-hydroxy-5Z,8Z,10E,14Z-eicosatetraenoic acid (12( S )-HETE), respectively 19 , 20 , play critical roles in the production of proinflammatory cytokines in lung airway disease in the context of asthma 21 . Despite the suggested role of the BLT2 cascade in lung inflammation, little is known about its contribution to the progression of lung cancer, especially KRAS-mutant lung cancer.…”
Section: Introductionmentioning
confidence: 99%